Introduction to Women's Studies (Kendall/Hunt Publishing Company, 2006)
Introduction to Women's Studies Section I Theory 1-- Section II Feminism Challenges the Academic Disciplines-- Section III Theoretical Transformations-- Section IV Redefining the Spaces of Women and Society